Carbon-neutral treatment of N, N-dimethylformamide-containing industrial wastewater by anaerobic membrane bioreactor (AnMBR): Bio-energy recovery and CO2 emission reduction. (August 2022) - Kong, Zhe; Xue, Yi; Hao, Tianwei; Zhang, Yanlong; Wu, Jiang; Chen, Hong; Song, Liuying; Rong, Chao; Li, Dapeng; Pan, Yang; Li, Yong; Li, Yu-You
Highlights: The AnMBR succeeded in the treatment of DMF-containing wastewater at 35 °C. High CH4 yield and COD removal are obtained by AnMBR during long-term operation. The AnMBR generated 3.45 kWh/m 3 of electricity from DMF-containing wastewater. The AnMBR could recover bio-energy by 607% while the CAS is energy-intensive. The AnMBR reduced 57.8% of CO2 emission than the CAS for treating DMF wastewater. Abstract: High-strength industrial wastewater containing approximately 2000 mg/L of N, N -dimethylformamide (DMF) was treated by the anaerobic membrane bioreactor (AnMBR) during a long-term operation with the concept of carbon neutrality in this study. Bio-methane was recovered as bio-energy or bio-resource from DMF-containing wastewater along with the CO2 emission reduction. The results are clear evidence of the feasibility of carbon–neutral treatment of DMF-containing wastewater by the AnMBR. With an effective degradation under the organic loading rate of 6.53 COD kg/m 3 /d at the HRT of 12 h, the AnMBR completely covered the energy consumption during long-term operation by saving electricity of 4.16 kWh/m 3 compared with the conventional activated sludge process. The CO2 emission of the AnMBR was just 1.06 kg/m 3, remarkably reducing 1.45 kg/m 3 of CO2 . The treatment of DMF-containing wastewater by the AnMBR perfectly realized the goal of carbon neutrality, and was considered as an alternative to the conventional activated sludge process.